Medidas e estudo de rádio propagação para TV digital na cidade de Belém - SILVA, Samara Pereira da (2018)
The telecommunications and broadcasting industry is undergoing major changes, due to increased search for access to digital multimedia data transmission services, especially through mobile systems. Mobile communications offer the possibility of a constant contact between users, providing easiness and conveniences such as quick access to information. For some time now, the mobile carriers and television broadcasters have been updating their systems, providing video conferencing services, internet and digital TV. The digital TV system emerges as the evolution of analog TV, mainly allowing a significant improvement in the quality of video and audio transmissions, strengthening concepts such as interactivity with viewers, signal reception in mobile devices and the possibility to broadcast several programs through the same channel. For this, it is imperative to solve one of the challenges of implementing digital broadcast television systems, which is determining whether the digital signal coverage will have the same range as it would have for an analog broadcasting, also accounting the cost effectiveness when balancing quality and signal strength. Therefore, by measuring campaigns in the UHF range (Ultra High Frequency) in the metropolitan region of Belém, it was collected a set of data which allowed the evaluation of methods of forecasting the average propagation loss in regions with Amazonic features, in which the study of loss involves an environment characterized by tropical climate and wooded suburban area with the presence of rivers. In this work we present a propagation average loss analysis from the measurements and the comparison with the forecasts provided for the same paths after implementing the Okumura-Hata model, ITU-R P.1546 and Free Space. It was our intention to describe the signal behavior and to verify the existence of appropriate models to characterize it. Finally, the results of simulations to obtain the loss and field strength profiles based on the experimental results are presented.